1997
DOI: 10.1002/ange.19971090828
|View full text |Cite
|
Sign up to set email alerts
|

Das Redoxpotential von Selenocystin in konformativ nicht eingeschränkten cyclischen Peptiden

Abstract: Selenocystein (Sec) kann, bezogen auf die ribosomenvermittelte Proteinsynthese, als die 21. Aminosaure betrachtet werden.", 21 Es kommt in vielen prokaryontischen und eukaryontischen Proteinen vor, wobei die Natur das UGA-Stopcodon zum Einfugen dieser Selenoaminosaure verwendet statt eines posttranslationalen Modifikationsmechanismus. Die meisten der bislang identifizierten Selenoproteine sind Redoxenzyme, die wegen des niedrigen pK,-Werts der Selenolfunktion (5.73 fur Sec, 8.53 [lo-171 Fragmentes in der o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
10
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…[22] Despite the similarity between Sec and Cys, a diselenide bond has a lower redox potential than a disulfide bond (À381 mV for SeÀSe and À181 mV for SÀS). [11,23] There is also a difference in nucleophilicity between the selenolate (Se À ) and thiolate (S À ) anions (pK a (Sec) = 5.24-5.63, pK a (Cys) = 8.25); hence, reactions with Sec occur much faster at lower pH values than reactions with Cys. [11] These properties suggest that, under acidic conditions, diselenidebond formation is favored over disulfide-bond formation.…”
mentioning
confidence: 98%
“…[22] Despite the similarity between Sec and Cys, a diselenide bond has a lower redox potential than a disulfide bond (À381 mV for SeÀSe and À181 mV for SÀS). [11,23] There is also a difference in nucleophilicity between the selenolate (Se À ) and thiolate (S À ) anions (pK a (Sec) = 5.24-5.63, pK a (Cys) = 8.25); hence, reactions with Sec occur much faster at lower pH values than reactions with Cys. [11] These properties suggest that, under acidic conditions, diselenidebond formation is favored over disulfide-bond formation.…”
mentioning
confidence: 98%
“…[5,6] A replacement of disulfide bridges by more redox-stable diselenide crosslinks has been employed for peptides containing either one or two disulfide bridges. [7][8][9][10][11][12] Substitution of a pair of cysteines with selenocysteines should guide the formation of disulfide bridges between the remaining cysteines, [8] because the more stable diselenide forms first (the redox potential of a diselenide bridge (E o = À381 mV) is significantly lower than that of a disulfide bridge (E o = À180 mV) [13] ) providing a topological constraint for the formation of the remaining disulfides and reducing the number of possible disulfide connectivities. [14] Once a disulfide-rich peptide is synthesized and oxidized, the disulfide bridges must be determined.…”
mentioning
confidence: 99%
“…We recently showed that redox buffers containing selenoglutathione (GSeSeG), which is a diselenide analogue of glutathione (GSSG), promote the oxidative folding of a wide range of proteins 2. Diselenides are thermodynamically more stable than disulfides3 but react more rapidly with thiols owing to the higher polarizability of selenium compared to sulfur 4. The greater acidity of selenols versus thiols (Δp K a ≈3)5 further enhances their reactivity.…”
mentioning
confidence: 99%
“…In fact, diselenides have been widely used as isosteric replacements of native disulfides in cysteine‐rich proteins, such as endothelins10 and conotoxins,11 to increase folding rates and yields while maintaining biological activity. Because diselenides have significantly lower reduction potentials than disulfides,3 their formation is favored thermodynamically, providing a powerful intramolecular constraint that ensures regioselective formation of correct cross‐links. Moreover, the diselenides increase the stability of these molecules to reduction and disulfide scrambling 11a,d.…”
mentioning
confidence: 99%